2016
DOI: 10.1177/0886260516673627
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Perceived Social Acknowledgment on the Relationship Between Patient Assaults and Posttraumatic Stress Reactions in Emergency Nurses

Abstract: This study explored whether posttraumatic stress symptoms resulted from workplace assaults were mediated by the perception of social acknowledgment by the victim. A sample of 444 emergency room nurses in China completed questionnaires measuring the frequency and types of patient assaults, the severity of physical injury, the perception of social acknowledgment, and the posttraumatic stress symptoms. Cross-sectional design, multiregression, and bootstrapping mediation analyses were used to test the hypotheses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…It is difficult to compare studies across different populations and different measures, but we believe that differences in the prospective findings could be due to the very different measurement periods and the fluctuating nature of PTSD 114 . Within studies of a shorter timeframe, the extant literature supports our present findings 21,23,111,112 . Our results are also in accordance with the theoretical framework proposed by McFarlane and colleagues, that states that PTSD can develop as a result of sensitization due to the cumulated Copyright © 2019 American College of Occupational and Environmental Medicine.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is difficult to compare studies across different populations and different measures, but we believe that differences in the prospective findings could be due to the very different measurement periods and the fluctuating nature of PTSD 114 . Within studies of a shorter timeframe, the extant literature supports our present findings 21,23,111,112 . Our results are also in accordance with the theoretical framework proposed by McFarlane and colleagues, that states that PTSD can develop as a result of sensitization due to the cumulated Copyright © 2019 American College of Occupational and Environmental Medicine.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, we found that frequency of violence did have a direct effect on PTSD(confirmation of H8) which is consistent with the definition of PTSD as a reaction to severely and threatening events 27 . We also found that frequency of violence was indirectly associated with However, our findings that frequency of OV was positively associated with PTSD symptoms have been shown in other cross sectional studies regarding emergency nurses 21 and mental health care professionals 111,112 . Only two studies have examined the prospective association of frequency of OV and PTSD.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Emergency nurses are routinely exposed to work-related traumatic events in their practice, such as severe injuries, death, suicide, and suffering, and also frequently encounter verbal and physical aggression from patients and their families ( Gillespie et al, 2013 ; Guan et al, 2019 ). These direct and indirect traumas may result in significant psychological consequences; importantly, emergency nurses have little time for recovery due to the emergency department’s hectic pace ( Gates et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study on a web-based intervention for social acknowledgement showed that social acknowledgement led to a reduction in PTSD symptomatology following a one-month intervention (Xu et al, 2016 ). Furthermore, in a recent study on patient assaults on Chinese emergency nurses, social acknowledgement was found to mediate the relationship between frequency of patient assaults and PTSD symptoms (Guan, Gao, Liu, Cheng, & Ge, 2019 ). To the best of the authors knowledge, only one study has previously examined social acknowledgement as a mediator of post-traumatic stress in an institutional sample (Krammer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%